From Macro to Micro: Large Exporters Coping with Common Shocks - Jean-Charles Bricongne; Juan Carluccio; Lionel Gérard Fontagné; Guillaume Gaulier; Sebastian Stumpner (Center for Economic Studies and ifo Institute (CESifo), 2022)
Since Gabaix (2011), the role of changes in the performance of some very large firms in shaping aggregate outcomes has been intensively studied in the economic literature. Changes in the performance of a few large firms can arise due to idiosyncratic shocks or idiosyncratic reactions to common shocks. This paper provides direct evidence for the second channel using data on the universe of French firm-level exports and imports over 1993-2020. Granularity matters for the micro-dynamics of aggregate French exports over the long run : the granular residual explains 42% of the variance in aggregate export growth during the period. Moreover, it co-moves with the macro shocks : the largest firms do better than average in good times and worse in bad times. Studying firm-level performance during the Great Financial Crisis and the Pandemic reveals that top exporters contributed to the export collapses disproportionably more than their pre-crisis share of exports, even within finely defined markets. We investigate the reasons for such over-reaction of the top exporters using the Pandemic as a natural experiment. We find that a higher elasticity to demand shocks explains the larger reaction of top exporters to the Pandemic, with GVC exposure having weak explanatory power. Our findings have macro implications, as they help understand the macro reaction to foreign shocks, and micro implications, since they can inform micro models of exports.
Keywords: F14; 330; granularity; exports; Covid crisis